Peran Kepuasan Pelanggan dalam Memediasi Pengaruh Product Quality, Brand Image, dan Brand Trust Terhadap Loyalitas Pelanggan Produk Sunscreen Azarine di Shopee: Studi pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Purwokerto - Talita Richi Stefani; Irawan Randikaparsa; Herni Justiana Astuti; Hermin Endratno (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study analyzes the influence of product quality, brand image, and brand trust on customer loyalty with customer satisfaction as a mediating variable in Azarine sunscreen consumers, which is based on Expectation Confirmation Theory as a theoretical basis in explaining the formation of consumer satisfaction and loyalty. The research method used in this study is a quantitative approach with a purposive sampling technique, namely a sampling technique based on certain criteria that have been determined in accordance with the research objectives. The number of respondents collected was 350 respondents, but 10 respondents were eliminated because they did not meet the research criteria, so the total sample used in the analysis was 340 respondents. Data were analyzed using Structural Equation Modeling–Partial Least Squares 3.0 (SEM-PLS 3.0). The results showed that product quality, brand image, and brand trust had a positive and significant effect on customer satisfaction. Subsequently, brand image and brand trust were proven to have a positive and significant effect on customer loyalty, while product quality did not have a significant direct effect on customer loyalty. Customer satisfaction was proven to be able to mediate the influence of product quality, brand image, and brand trust on customer loyalty. These findings indicate that companies need to ensure product quality meets consumer expectations, maintain a positive brand image, and increase customer trust to ensure consumer satisfaction and increase customer loyalty sustainably.